1972
DOI: 10.1128/iai.5.4.537-541.1972
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dihydrostreptomycin on Phagocytosis of Mouse-Peritoneal Macrophages In Vitro

Abstract: The effect of the antibiotic dihydrostreptomycin on the phagocytic and bactericidal ability of peritoneal macrophages obtained from mice has been investigated. In subliminal concentrations which did not influence the bacterial growth, the drug caused macrophages to ingest and kill bacteria ( Escherichia coli ) at a higher rate than did macrophages without antibiotic. The differences for phagocytosis and intracellular killing of E. coli with and without a sublimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1973
1973
1993
1993

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…It has been shown, however, that the effect is not due to action on the macrophages themselves (1). It is important to note that the antibiotics enhanced phagocytosis of unrelated microorganisms, L. monocytogenes, as shown here, and Escherichia coli, as shown previously (1). Antibiotics of different modes of action yielded similar results.…”
Section: Resultssupporting
confidence: 88%
“…It has been shown, however, that the effect is not due to action on the macrophages themselves (1). It is important to note that the antibiotics enhanced phagocytosis of unrelated microorganisms, L. monocytogenes, as shown here, and Escherichia coli, as shown previously (1). Antibiotics of different modes of action yielded similar results.…”
Section: Resultssupporting
confidence: 88%
“…This is in keeping with the report of Bonventre and Imhoff (3) that streptomycin is steadily concentrated in macrophages over a period of 6 days. Recently, Adam et al (1) reported a rapid enhancement in the destruction of bacteria by macrophages when phagocytosis is allowed to proceed in the presence of subliminal amounts of streptomycin. In the present exl)eriments, the penetration of small amounts of antibiotics into the macrophages may have beeil sufficient to l)revent bacterial division.…”
Section: Resultsmentioning
confidence: 99%
“…An antibiotic mixture utilized to eliminate adherent or extracellular bacteria is not internalized, nor is it present throughout the postengulfment period when resident or exocytosed organisms are removed by periodic washing of the culture. By effectively controlling unphago- Resident 1 (1) 1 (1) 1 (1) Thioglycolate 16 (2) NDC ND Fetal calf serum 11 (2) ND ND Listeria antigen 12 (1) 1 (1) 1 (1) Listeria immune 1 (1) 1 (1) 1 (1) Immune Listeria antigen 5 (1) 6 (1) 5 (1) elicited Immune thioglycolate elicited 12 (2) 5 (1) 2 (1) Immune fetal calf serum 1 (1) 1 (1) 1 (1) elicited a Peritoneal cells were collected from mice treated intraperitoneally 1 day previously with 1 ml of fetal calf serum or 5 days previously with either 1 ml of 3% fluid thioglycolate or 106 heat-killed Listeria (antigen) and from 7-day Listeria-immune animals elicited with either antigen, thioglycolate, or fetal calf serum 18 h before assay.…”
Section: Discussionmentioning
confidence: 99%
“…In many instances, it is not clear whether immune macrophages in culture are bactericidal, bacteriostatic, or merely capable of inhibiting the rate ofintracellular bacterial growth. Several studies indicate that macrophage antibacterial activity may be an artifact of the internalization of drugs utilized to restrict the growth of adherent or unphagocytized bacteria in the cultivation medium (1,9,21). Determinations of intracellular killing may also be confused with extracellular bacterial sterilization by secretory products of activated macrophages (3,19).…”
mentioning
confidence: 99%